1978
DOI: 10.1080/00015127809435177
|View full text |Cite
|
Sign up to set email alerts
|

Lipids and Proteins in Eggs and Blood Serum from two Strains of Hens

Abstract: IntroductionIn evaluating genetic improvement of the egglaying capacity of hens !ittle attention has been given t o date t o the internal composition of the eggs. For marketing purposes eggs are usually classified only by size, shell strength, and whatever can be seen by passing light through them. Therefore breeders have little incentive t o obtain any changes in the internal composition.Recently Rodda et al. (1977) has reported some genetic relation between egg weight and conipositional traits and several pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1980
1980
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…It becomes evident that advances in hen breeding for egg-production capacity result in decreasing cholesterol content in egg yolk. As BARTOV et al [3], BAIR et al [4] and ROTENBERG et al [5] noted, an increased egg-production rate had pronounced effects on decline in yolk cholesterol content. With highly productive laying hybrids, SEMJANOVA et al [6] showed that this relationship was expressed by a correlation coefficient r = -0.619.…”
Section: Introductionmentioning
confidence: 98%
“…It becomes evident that advances in hen breeding for egg-production capacity result in decreasing cholesterol content in egg yolk. As BARTOV et al [3], BAIR et al [4] and ROTENBERG et al [5] noted, an increased egg-production rate had pronounced effects on decline in yolk cholesterol content. With highly productive laying hybrids, SEMJANOVA et al [6] showed that this relationship was expressed by a correlation coefficient r = -0.619.…”
Section: Introductionmentioning
confidence: 98%